Pelatihan manajemen keuangan bagi mustahik di Kampung Zakat Desa Nyalabu Daya Pamekasan - Rohmaniyah, Wasilatur; Halida, Uly Mabruroh; Rahmawati; Masiyah, Riayatul (IAIN Madura, 2025)
Low levels of financial literacy and poor financial management skills remain key challenges faced by the “mustahik” (zakat beneficiaries), particularly those engaged in Micro, Small, and Medium Enterprises (MSMEs). This condition hinders the optimal utilization of zakat funds to support sustainable economic development among the mustahik. This community engagement program aimed to enhance the financial literacy and managerial skills of the mustahik in the Zakat Village (Kampung Zakat) of Nyalabu Daya Village, Pamekasan, through participatory-based financial management training. The underlying hypothesis of the program is that improved financial literacy can lead to a shift in mindset, which in turn can positively influence financial behaviour and significantly enhance the economic independence of the mustahik. The program adopted a Participatory Action Research (PAR) approach, actively involving the mustahik in problem identification, solution design, training, and evaluation. The training focused on practical skills such as budgeting, setting financial priorities, recordkeeping, and separating personal and business finances. The results showed significant improvement in participants’ ability to manage their business finances in terms of mindset transformation and technical capabilities. Participants also demonstrated greater confidence in managing their businesses independently and sustainably. These findings support the theory that participatory approaches enhance the effectiveness of learning and empowerment in community-based settings. This program is recommended for replication in other mustahik communities as a sustainable, zakat-based model for economic empowerment through structured financial education.[Rendahnya tingkat literasi dan kemampuan manajemen keuangan merupakan salah satu tantangan utama yang dihadapi oleh mustahik, terutama mereka yang menjalankan usaha skala mikro, kecil, dan menengah (UMKM). Kondisi ini berdampak pada kurang optimalnya pemanfaatan dana zakat untuk meningkatkan keberlanjutan ekonomi mustahik. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan literasi keuangan dan keterampilan manajerial mustahik di Kampung Zakat, Desa Nyalabu Daya, Pamekasan, melalui pelatihan manajemen keuangan berbasis partisipatif. Hipotesis yang mendasari program ini adalah bahwa peningkatan literasi keuangan akan mendorong perubahan pola pikir sehingga berdampak pada perubahan perilaku keuangan serta meningkatkan kemandirian ekonomi mustahik secara signifikan. Program ini menggunakan pendekatan Participatory Action Research (PAR), yang melibatkan mustahik secara aktif dalam proses identifikasi masalah, perancangan solusi, pelatihan, dan evaluasi. Kegiatan difokuskan pada keterampilan penyusunan anggaran, penentuan skala prioritas, pencatatan keuangan, serta pemisahan keuangan usaha dan pribadi. Hasil penelitian menunjukkan peningkatan yang signifikan dalam kemampuan peserta mengelola keuangan usaha, baik dari sisi perubahan pola pikir maupun aspek teknis. Peserta juga menunjukkan peningkatan kepercayaan diri dalam mengelola usaha secara mandiri dan berkelanjutan. Temuan ini mendukung teori bahwa pendekatan partisipatif dapat memperkuat efektivitas pembelajaran dan pemberdayaan dalam konteks komunitas. Program ini direkomendasikan untuk direplikasi pada komunitas mustahik lainnya sebagai model pemberdayaan ekonomi berbasis zakat yang berkelanjutan dan berbasis edukasi keuangan.]